Evaluating the Implementation of a Model of Integrated Behavioral Health in Primary Care: Perceptions of the Healthcare Team - Julia Alexandra Dunn; Hélène Chokron Garneau; Nadine Jawad; Mira Zein; Kirsti Weng Elder; Amelia Sattler; Mark McGovern (SAGE Publishing, 2023)
Objectives: This study aims to compare primary care providers and medical assistants in degrees of comfort, confidence, and consistency when addressing behavioral health concerns with patients before and after the implementation of a model of integrated behavioral health in primary care (IBHPC), and evaluate whether these perceptions differ based on increased access to behavioral health clinicians. Methods: This longitudinal study was conducted at 2 primary care clinics in Northern California while implementing an IBHPC model. The Integrated Behavioral Health Staff Perceptions Survey was administered to assess the comfort, confidence, and consistency of behavioral health practices. Confidential online surveys were distributed to primary care faculty and staff members before and post-implementation. Responses from providers and medical assistants were compared between pre- and post-implementation with linear regression analyses. The relationships between accessibility to behavioral health clinicians and a change in comfort, confidence, and consistency of behavioral health practices were explored using a linear mixed-effects model. Results: A total of 35 providers and medical assistants completed the survey both before and post-implementation of IBHPC. Over time, there were increasingly positive perceptions about the consistency of behavioral health screening ( P  = .03) and overall confidence in addressing behavioral health concerns ( P  = .005). Comfort in addressing behavioral health concerns did not significantly change for either providers or staff over time. Medical assistants were initially more confident and comfortable addressing behavioral health concerns than providers, but providers' attitudes increased post-IBHPC implementation. Improved access to behavioral health clinicians was associated with greater consistency of screening and referral to specialty mental health care ( P  < .001). Conclusion: The present study is the first to explore differences in provider and medical assistant perceptions during the course of an IBHPC implementation. Findings underscore the importance of integrating medical assistants, along with providers, into all phases of the implementation process.